Global Panoramic analysis of clinical research in cell therapy: clinical trial landscape, marketed products, and regulatory trends - Wang, Mengmeng; Zhou, Tiange; Liu, Sijia; Xiang, Wanwan; Xie, Kewen; Zhang, Xiaoqiong; Hu, Wenxin; Fang, Mengling; Zhang, Ziyue; Chen, Meimei; Wang, Xi; Wu, Jiancai (Frontiers in Pharmacology, 2026)
IntroductionCell therapy is a vital field in modern medicine. This review assesses its global clinical development landscape, approved products, and regional regulatory characteristics.MethodsA comprehensive search and analysis of global clinical trial databases (e.g., https://clinicaltrials.gov/ClinicalTrials.gov), regulatory agency announcements, and relevant literature up to October 2025 was conducted. Key data points regarding trial numbers, phases, therapy types, and approved products were extracted and analyzed descriptively by region.ResultsA cumulative total of 10,373 cell therapy clinical trials were identified worldwide, with primary distribution across the United States (3,563 trials), China (3,365 trials), and Europe (1,584 trials). Oncology (56.1%) and immune system diseases (9.3%) were the main research focuses. Immune cell therapy (5,167 trials) and stem cell therapy (4,796 trials) received comparable attention, with CAR-T therapy (2,409 trials) being prominent within the former, and mesenchymal stem cells (MSCs, 1,904 trials) and hematopoietic stem cells (HSCs, 1,550 trials) dominating the latter. Since 2016, China has led in the number of clinical trials, particularly in CAR-T research. Europe had a significantly higher proportion of Phase III trials compared to China and the US. The US led in the approval of HSC-based drugs. Approved immune cell drugs are predominantly CAR-T products for hematological malignancies, originating mainly from the US and China. Approved stem cell drugs are primarily HSC and MSC products, authorized in the US, Japan, South Korea, and China, covering indications such as graft-versus-host disease. Other somatic cell therapies are established for skin repair, bone disorders, and ophthalmology, with South Korea leading in skin-related products.DiscussionThese findings reveal distinct regional strengths and strategic emphases in cell therapy development. The observed patterns are significantly influenced by heterogeneous regulatory frameworks across regions. The global industry is advancing the translation of cell therapy from cutting-edge technology to accessible clinical application through the synergy of scientific innovation and evolving regulatory pathways.